SERVIÇO SOCIAL NO SISTEMA PENITENCIÁRIO: ASPECTOS TEÓRICO-METODOLÓGICOS NO CONTEXTO DA REINSERÇÃO SOCIAL - dos Santos Neto, Francisco; Sebastiana da Conceição Braga , Cilene (Revista Serviço Social em Perspectiva, 2022)
This article aims to highlight theoretical and methodological aspects of the professional practice of social workers in the Brazilian Penitentiary System, particularly in the Social Reinsertion policy provided for in Law nº. 7210/1984 on Penal Execution. This analysis is based on reflections built from professional experience as a Social Worker in Penitentiary Management at the State of Pará Penitentiary Administration (SEAP). The research was based on the bibliographic and documentary survey / research, as well as participant observation. As a preliminary result, it was found that the competences and requests placed on Social Service in the organ have a character strongly influenced by conservatism there is a precarization process of work expressed, mainly due to the insufficient number of professionals to serve the population that uses the services; while it shows a field of interventional possibilities mediated the formative principles of the vocational training project of the Brazilian Association of Education and Research in Social Work (ABEPSS).